Estimated Birth Weight by current Weight-and Age During the First Five Days of Life - Siswanto Agus Wilopo; Mohammad Hakimi; Achmad Surjono (Indonesian Pediatric Society, 1993)
In the developing countries, measurement of birth weight is subjected to methodological problems. The main issue is the difficulty of measuring birth weight soon after delivery. Two relevant questions are proposed by this study : 1) can a birth weight be estimated several hours or days after a baby was delivered ?, and 2) can an estimated birth weight be collected by paramedical personnel with reliable results? To answer these questions, we conducted a study at Dr. Sardjito Hospital, Yogyakana, to evaluate agreement between two paramedical personnel in the routine measurements of neonatal weight in the rooming-in ward. The behavior of these two paramedical personnel was observed from one month when they examined 32 neonates. Both of them weighed the neonate at 7.00 hours and one weighed the neonate at 15.00 or 21.00 hours. The order of the last two measurements was made alternatingly. This resulted in 156 pairs of measurement for agreement analysis. There was a strong evidence that the two raters have almost perfect agreement on measuring neonatal weights (intraclass correlation coefficient = 0.978). The second part of this study looked at neonatal weight during the first five days of life. The neonatal weights were measured three times a day up to age of the days. We constructed a formula for estimating their birth weight based on a current neonatal weight and age in days. Birth weight can be estimated using formula : Birth weight ; 51 + 1. 029 x current weight - 10 x age in days. The data fitted very well to this least square estimate with a coefficient of determination (R) = 0.95.